Modelling of beta-D-glucopyranose ring distortion in different force fields: a metadynamics study - Spiwok, Vojtech; Králová, Blanka; Tvaroska, Igor (Carbohydrate research, 2010)
Modelling of carbohydrate conformations is a challenging task for force field developers. Three carbohydrate force fields, namely GLYCAM06, GROMOS 45a4 and OPLS were evaluated. Free energies of different ring conformations of beta-D-glucopyranose were calculated using metadynamics in vacuum as well as in explicitly modelled water. All three force fields model the (4)C(1) conformation as the most stable by at least 6kJ/mol, as compared to other conformations. Interconversion from the (4)C(1) to any other conformation is associated with a barrier of no lower than 26kJ/mol. The free energy surface calculated in the GLYCAM06 force field is in remarkably good agreement with the recent Car-Parrinello metadynamics study. The effect of a water environment is relatively low and analogous in all tested force fields. Namely, the presence of water stabilizes the upper-left ((3,O)B) versus bottom-right (B(3,O)) area of Stoddard's plot, relative to the situation in vacuum. Comparison of free and potential surfaces is also provided for vacuum calculations.
Keywords: Thermodynamics; Molecular Dynamics Simulation; voda; konformace sacharidů; Glucosides; Water; simulace molekulární dynamiky; termodynamika; Carbohydrate Conformation; glukosidy